Influence of habitual practice of physical activity and trunk fat on fasting glucose in postmenopausal women - Buonani, Camila [UNESP]; Rossi, Fabrício E. [UNESP]; Diniz, Tiego A. [UNESP]; Christofaro, Diego G. D. [UNESP]; Fernandes, Rômulo A. [UNESP]; Freitas Jr., Ismael F. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
Study Model: Original Study. Objective: To examine the relationship between the practice of physical activity (PA) with total body fat, trunk fat and fasting glucose in postmenopausal women. Methods: Sixty postmenopausal women, mean age of 61.0 years, from the city of Presidente Prudente SP, were assessed. Body mass (BM) and height were measured to calculate Body Mass Index (BMI). Total body fat (BF) and trunk fat mass (TFM) were estimated using DEXA. Fasting glucose was measured and classified according to the reference values of the American Diabetes Association (1997). The usual practice of PA was estimated using triaxial accelerometer, model GT3X (Actigraph, Pensacola, FL, USA) and classified according to Sasaki (2010). Comparisons were made between women with normal blood fasting glucose levels (NBG) and high blood fasting glucose(HBG) levels by the Kruskal-Wallis test. Spearman correlation coefficient was used and then the binary logistic regression to test the association between PA level and body composition with fasting glucose. Results: Women with HBG showed higher values of BM (p=0.040), BMI (p=0.002) and BF (p=0.046), and lower values of light (p=0.019), moderate (p=0.041) and moderate+vigorous (p=0.041) PA. The moderate and moderate+vigorous PA showed, respectively, a significant negative correlation with BF (p=0.003 and p=0.003) and TFM (p=0.021 and p=0.021). The FM presented negative correlation with moderate+vigorous (p=0.049). Women with lower TFM and classified as active showed protective factor (OR=0.133 [CI 0.023 to 0.784]) for impaired fasting glucose. Conclusion: The practice of moderate+vigorous intensity PA, held at least 150 minutes per week, is associated with lower trunk fat, and presents protective factor for impaired fasting glucose and risk of diabetes mellitus in postmenopausal women.
Influência da prática habitual de atividade física e da gordura de tronco sobre a glicemia de jejum em mulheres na menopausa
Keywords: Accelerometer; Hyperglycemia; Physical activity; Postmenopause